2011
DOI: 10.1002/etc.595
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of cadmium and zinc impact their toxicity to the earthworm Aporrectodea caliginosa

Abstract: Individual and binary mixture effects of Cd and Zn on mortality of the earthworm Aporrectodea caliginosa were investigated in one soil type. Mutual, systemic interactions of Cd and Zn were assessed over a broad range of concentration combinations. Exposures were expressed as measured total concentrations in soil, porewater concentrations, and CaCl(2)-extractable concentrations. The Cd-Zn and Zn-Cd interactions in soil were estimated by comparing partition coefficients (K(d)) of one metal in the presence and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…It should be noted that both the concentration addition model and the independent action model in their standard form do not consider mixture interactions in estimating mixture toxicity. However, mixture components may interact at various levels: 1) exposure level, 2) uptake level, and 3) target level . Identifying interactions at relevant levels will therefore help to explain differences in interaction patterns that occur between different exposure media and between different test organisms.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that both the concentration addition model and the independent action model in their standard form do not consider mixture interactions in estimating mixture toxicity. However, mixture components may interact at various levels: 1) exposure level, 2) uptake level, and 3) target level . Identifying interactions at relevant levels will therefore help to explain differences in interaction patterns that occur between different exposure media and between different test organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The binary mixture effects of cadmium and zinc on the mortality of Aporrectodea caliginosa were also investigated by Qiu et al . [14]. They reported that the effects of the cadmium and zinc mixtures on the mortality of Aporrectodea caliginosa were mainly antagonistic, and the magnitude of the antagonism was dependent upon both the relative concentrations of cadmium and zinc and their concentration magnitudes.…”
Section: Effects Of Metals On Earthwormsmentioning
confidence: 99%
“…Traditional ecotoxicological studies were often performed for a certain endpoint after a fixed exposure time (Lock and Janssen, 2002;Qiu et al, 2011), while toxicity may vary with time. For instance, Utgikar et al (2004) and Baas et al (2007), investigating the mixture toxicity of Zn and Cu to Vibrio fischeri and of Cu and Cd to Folsomia candida, respectively, found that the toxicity of these metal mixtures increased with exposure time.…”
Section: Introductionmentioning
confidence: 99%